Nitrogen and carbon dioxide fracturing fluids for the stimulation of unconventional shale plays - Palmer, Candice; Sito, Zbigniew (My University, 2013)
With the International Energy Agency (IEA) projecting that the global demand for natural gas to increase by 50% from 2010 to 2035, the exploration of unconventional gas reserves (e.g. shale gas, tight gas and coal bed methane) will gain increasing importance as conventional gas reserves become more depleted. To enhance the production of unconventional gas and oil, water-based fracturing fluids are extensively used for the stimulation of North American shale plays because they are inexpensive and offer excellent proppant transport into the fracture when used with gelled polymers. However, in circumstances where water-based fracturing fluids are unsuitable due to concerns related to water sensitivity and clay swelling, alternative fracturing fluids are used such as nitrogen and carbon dioxide treatments. Nitrogen and carbon dioxide fracturing fluids are particularly advantageous in depleted and shallow formations because they offer a non-damaging effect around the fracture, rapid cleanup of flowback fluid, and reduced water requirements compared to conventional water-based fracturing fluids. Much research has been published about water-based fracture treatments, therefore, this review paper considers the use of nitrogen and carbon dioxide fracturing fluids used for the stimulation of unconventional shale plays, mainly in North America. By analysing selected literatures studies, this review paper summarises the utilization of the various types of nitrogen and carbon dioxide treatments (i.e. straight gas, foam, energized, cryogenic liquids) across various shale plays such as the Montney play, the Devonian play, and the Marcellus play. The paper further identifies the major benefits and challenges of nitrogen and carbon dioxide treatments documented by well operators, which will facilitate knowledge transfer about the applicability of nitrogen and carbon dioxide fracturing fluids.
AGH Drilling, Oil, Gas
Keywords: nitrogen; carbon dioxide; fracturing fluids; shale gas